The influence of salinity increasing on the fish communities in the east of Al-Hammar marsh- southern Iraq - Al-Najjar, Ghassan, A. (Iraqi Journal of Aquaculture, 2019)
The study included the effect of the advancement of the saline front on the composition of the fish catchment of the East Hamar marsh for the period from January 2018 to December 2018. Three stations were chosen, namely Harir, Al-Salal and Al-Baraka. 27673 individuals caught the first and second stations together, of which 9178 marine individuals and the rest of us are river fish. As for the third station, it collected 21,741 individuals, of which 5021 were marine individuals, as the total number of species reached 35 species for the two stations of silk and sila, including 21 marine species and 14 river types were obtained 20 species in the third station. The pond, of which 7 are marine, and 13 river species. The Minnows Thryssa whiteheadi showed dominance in the first station, whereas Poecilia latipinna was in second place, and the family of tilapia Cichlidae formed the third position in the arrangement. As for the second and third stations, sovereignty of a family Cichlidae tilapia as recorded A noticeable increase in the numbers of yellow guilt Acanthopagrus arabicus and Liza klunzingeri Al Bayha fish. The high salinity levels have led to the disappearance of freshwater fish, especially local fish.